Localized policy design for clean heating transitions: a multi-city analysis of renter preferences for energy efficiency - Troxell, Graeme; Conrad, Steve; Sussman, Reuven (Frontiers in Environmental Science, 2025)
IntroductionThe transition to clean heating systems in rental housing is crucial for achieving net-zero emissions goals, yet current policy frameworks lack systematic understanding of how renter preferences vary across different market contexts. While existing research acknowledges split incentive barriers between landlords and tenants, analysis of their manifestation across diverse demographic groups and market conditions remains notably absent.MethodsThis study employs latent class analysis of discrete choice experiment data from the American Council for an Energy-Efficient Economy to identify distinct renter segments and their responses to energy-efficient rental options. Our study combines demographic analysis with market valuation techniques to examine how renter segments distribute across three diverse metropolitan areas—San Diego, Houston, and Durham.ResultsThe analysis identifies six differentiated renter classes, characterized by systematic variation in demographic factors, housing preferences, and economic indicators. We find that while initial return multipliers exhibit significant sensitivity to assumptions about rent and energy cost differentials, the financial burden for energy-inefficient rentals is considerably larger than the premium one might pay for efficient rentals (presenting a penalty-to-premium of 1.35–1.42). The proportion of housing costs captured by landlords versus utilities varies significantly by market, increasing from 78.4% to 87.1% in San Diego, 74.9%–89.1% in Houston, and 88.5%–94.1% in Durham as properties move from poor to high efficiency, highlighting how regional characteristics shape the distribution of improvement costs between landlords and tenants.DiscussionThe study demonstrates how demographic composition systematically influences clean heating transition opportunities across rental markets, provides empirical evidence of geographic variation in renter segment distribution, and quantifies market-specific responses to efficiency improvements. These findings also underscore a market asymmetry that can impede extensive energy retrofits and enable policymakers to develop targeted approaches for accelerating clean heating adoption while maintaining affordability across diverse renter populations.